Could women outrun men in ultramarathon races? - Bam, J.; Noakes, T. D.; Juritz, J.; Dennis, S. C. (Medicine & Science in Sports & Exercise, 1997)
To test a hypothesis that the differences in running performances between men and women narrow with increasing race distance, recent best running speeds (m.s-1) of 28 female ultramarathon runners over racing distances from 5 to 90 km were compared with those of male runners matched for 56 km race time, age and training. These comparisons revealed that the men ran faster than the women over 5 to 42.2 km (P < 0.01-0.05), but not in a 90-km race (2.82 +/- 0.04 vs 2.90 +/- 0.09 m.s-1). Declines in the men's and women's running speeds with increasing race distances were best fitted by Y = 2.9.exp.(-0.01.X) + 1.7 and Y = 2.1.exp.(-0.01.X) + 2.0 equations (r = -0.99). Differences between the exponential declines in the men's and women's running speeds over longer race distances were best fitted by a linear Y = -0.006 (X-66) equation (r = -0.98, P < 0.001). The negative slope and the X-axis intercept of this equation at 66 km supports the hypothesis that women ultramarathon runners have greater fatigue resistance than do equally trained men whose performances are superior up to the marathon distance.